Conjunctival FOXP3 expression in trachoma: do regulatory T cells have a role in human ocular Chlamydia trachomatis infection? - Nkoyo Faal; Robin L Bailey; David Jeffries; Hassan Joof; Isatou Sarr; Mass Laye; David C W Mabey; Martin J Holland (PLoS Medicine, 2006)
Trachoma, caused by ocular infection with Chlamydia trachomatis, remains the leading infectious cause of blindness and in 2002 was responsible for 3.6% of total global blindness. Although transmission can be successfully interrupted using antibiotics and improvements in public and personal hygiene, the long-term success of the control programmes advocated by the World Health Organization are still uncertain. For the complete control and prevention of trachoma, a vaccine would be highly desirable. Currently there are no licensed vaccines for trachoma, and no human vaccine trials have been conducted since the 1960s. A barrier to new attempts to design and introduce a vaccine is the identification of immunologic correlates of protective immunity or immunopathology. We studied important correlates of the immune response in a trachoma-endemic population in order to improve our knowledge of this disease. This is essential for the successful development of a vaccine against both ocular and genital C. trachomatis infection.We used quantitative real-time PCR for C. trachomatis 16S rRNA to identify conjunctival infection. The expression of IFN-gamma, IDO, IL-10, and FOXP3 mRNA transcripts was measured. We evaluated the role of immune effector and regulatory responses in the control of chlamydial infection and in the resolution of clinical signs of trachoma in endemic communities in Gambia. All host transcripts examined were detectable even in normal conjunctiva. The levels of these transcripts were increased, compared to normal uninfected conjunctiva, when infection was detected, with or without clinical disease signs. Interestingly, when clinical disease signs were present in the absence of infection, the expression of a regulatory T cell transcription factor, FOXP3, remained elevated.There is evidence of an increase in the magnitude of the local anti-chlamydial cytokine immune responses with age. This increase is coupled to a decline in the prevalence of infection and active trachoma, suggesting that effective adaptive immunity is acquired over a number of years. The anti-chlamydial and inflammatory immune response at the conjunctival surface, which may control chlamydial replication, is closely matched by counter inflammatory or regulatory IL-10 expression. Differences in the level of FOXP3 expression in the conjunctiva may indicate a role for regulatory T cells in the resolution of the conjunctival immune response, which is important in protection from immunopathology. However, the expression of cytokines that control chlamydial replication and those that regulate the conjunctival immune response is not simply juxtaposed; the interaction between the infection and the clinical disease process is therefore more complex.